An Analysis of the Differences of Marital Adjustment among Educated Career and Non-career Women in Bangladesh - Akhter, Shammi (International Journal of Social Sciences and Management, 2021)
Present study aimed to explore the differences of marital adjustment among educated women in Bangladesh, especially career or dual career married women and non-career or housewives. The study has focused on both qualitative and quantitative approach or mixed method to address the aforesaid issue. Field survey and face to face interview technique was used for data collection. A sample of fifty educated women (twenty-five career and twenty-five non-career women) was selected based on purposive sampling technique and a detailed interview schedule was constructed in this regard. This study revealed that higher educational qualification of husband and wife, increased marital cohesions and harmonies, dissolution and duration of marriage are very important for marital adjustment. Marital adjustment is an important area of research as it promotes emotional stability, intellectual efficiency, and social effectiveness. Int. J. Soc. Sc. Manage. Vol. 8, Issue-2: 372-379